Animated Web Series as Media for Islamic Education in Children: Web Series Animasi sebagai Media Pendidikan Islami pada Anak - Langga, Fathin Hanifah; Ahmad, Hafiz Aziz; Mansoor, Alvanov Z. (Universitas Muhammadiyah Sidoarjo, 2020)
Islamic education needs to be taught to everybody since an early age so they can understand, have moral and noble character which can be embedded since young. In the current era of technological development, the internet has an important role for communities, especially for parents in delivering Islamic education to children. Video-based social media called Youtube is the choice of entertainment and education media for children. Some of the shows on Youtube that are mostly chosen to deliver Islamic education to children are Nussa’s animated web series, Syamil Dodo and Kastari Senja. The purpose of this study is to find out the three animations in fulfilling the criteria of educational media in conveying the message of Islamic education in accordance with the goals of national education, interpretation of the Qur’an and its benefit as an educational medium. The study used qualitative descriptive method. The findings from this study are Nussa animation, Syamil Dodo and Kastari Senja can provide the contents of the message of Islamic education in accordance with the criteria for national educational goals. On the criteria of educational media based on the interpretation of the Qur’an, the Nussa animation best meets the criteria as a medium for delivering good Islamic education. While animations that have fulfilled as an educational medium are the animation of Syamil Dodo and Kastari Senja. In conclusion, Nussa animation is the animation that best meets the criteria as an Islamic educational medium compared to Syamil Dodo and Kastari Sentra.